2018
DOI: 10.1177/0033688217750642
|View full text |Cite
|
Sign up to set email alerts
|

Teaching of English as an International Language in Various Contexts:Nothing is as Practical as Good Theory

Abstract: Despite the proliferation of publications on teaching English as an international language (EIL) or a Lingua Franca (ELF), the diffusion of these concepts into the world of English Language Teaching has been slow and incomplete. There is some wariness among educators about the teaching of ELF and EIL, with no consensus regarding appropriate pedagogy. In this article we look at some of the research on the integration of global Englishes into English language classrooms and discuss issues concerning a model of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Culture is an indispensable component of learning and teaching a language (Byram, 1997;Dogancay-Aktuna & Hardman, 2018;Kramsch, 1993). The teaching of culture in the EIL context has been the subject of intense debate in the research on teaching English as a foreign language (Tan & Farashaiyan, 2016).…”
Section: Culture In Eilmentioning
confidence: 99%
“…Culture is an indispensable component of learning and teaching a language (Byram, 1997;Dogancay-Aktuna & Hardman, 2018;Kramsch, 1993). The teaching of culture in the EIL context has been the subject of intense debate in the research on teaching English as a foreign language (Tan & Farashaiyan, 2016).…”
Section: Culture In Eilmentioning
confidence: 99%
“…Still, many teachers are concerned about how to incorporate these dimensions into ELT (Dogancay-Aktuna & Hardman, 2018;Rajprasit, 2021;Wang et al, 2021) and into the Saudi context specifically (Bukhari, 2019). Although research in Global Englishes is established in European and Asian region, recent studies have reported the scarcity of Global Englishes-related research in the conservative context of Saudi Arabia (Bukhari, 2019;Elyas & Mahboob, 2020;Elyas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The global spread of English and the current Sociolinguistic realities have led to the emergence of the various frameworks "to conceptualize, research and teach English" [1]. These frameworks i.e.…”
Section: Introductionmentioning
confidence: 99%